2001
DOI: 10.1053/jlts.2001.21457
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of serious graft damage induced by de novo hepatitis B virus infection after liver transplantation

Abstract: De novo hepatitis B virus (HBV) infection after orthotopic liver transplantation (OLT) is commonly believed to be a relatively benign condition, in contrast to post-OLT infection recurrence, considered a very aggressive complication. We reviewed the charts of 569 non-HBV-related OLTs performed at our institution and identified 19 patients (3%) with de novo HBV infection (appearance of hepatitis B surface antigen [HBsAg] after OLT). After a median follow-up of 25 months beyond the detection of HBsAg, 12 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…However, follow-up biopsies in this series revealed significant histologic recurrence in 5 out of 8 biopsies from 1.6 to 4.5 years after LT and an overall decreased 4-year survival in recipients of grafts from anti-HBc donors (1). Other authors in addition have reported more severe disease including Uemoto et al who described 15 cases with one death from fibrosis cholestatic hepatitis and two with chronic active hepatitis (3,10,41). The effect of new antiviral therapies and antiviral-resistant HBV infections on the course of de novo post-LT HBV is yet to be determined.…”
Section: Yen Et Almentioning
confidence: 54%
“…However, follow-up biopsies in this series revealed significant histologic recurrence in 5 out of 8 biopsies from 1.6 to 4.5 years after LT and an overall decreased 4-year survival in recipients of grafts from anti-HBc donors (1). Other authors in addition have reported more severe disease including Uemoto et al who described 15 cases with one death from fibrosis cholestatic hepatitis and two with chronic active hepatitis (3,10,41). The effect of new antiviral therapies and antiviral-resistant HBV infections on the course of de novo post-LT HBV is yet to be determined.…”
Section: Yen Et Almentioning
confidence: 54%
“…All recipients were anti-HBc negative. Segovia et al [15] reported a higher and more aggressive de novo HBV infection in 12 out of 19 patients. Three recipients were anti-HBc positive, and nine were anti-HBc negative.…”
Section: Historical Perspectivementioning
confidence: 95%
“…Despite this high rate of transmission, most studies have shown that patients with de novo HBV infection usually have a mild clinical course and infection can be prevented with prophylaxis [15,32•]. However, a recent study from Spain demonstrated that 63% of patients developed severe de novo HBV infection and 21% died, demonstrating that de novo HBV can have an aggressive course [15].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
See 2 more Smart Citations